Cohort profile: the Scottish Research register SHARE. A register of people interested in research participation linked to NHS data sets. Issue 2 (1st February 2017) - McKinstry, Brian; Sullivan, Frank M; Vasishta, Shobna; Armstrong, Roma; Hanley, Janet; Haughney, John; Philip, Sam; Smith, Blair H; Wood, Amanda; Palmer, Colin N A
Abstract : Purpose: Recruitment to trials is often difficult. Many trials fail to meet recruitment targets resulting in underpowered studies which waste resources and the time of those who participated. While there is evidence that many people are willing to take part in research, particularly if it involves a condition from which they suffer, researchers are unable to easily contact such people often relying on busy clinicians to identify them. Many clinicians perceive themselves as too busy to take part in research activities. The Scottish Health Research Register SHARE adopts an approach which asks the public to consent to their data held in National Health Service databases to be used to determine their suitability for research projects. Additionally, participants can consent for spare blood, left after routine venepuncture to be automatically identified in the laboratory and stored for future research studies. Participants: Anyone over the age of 16 years in Scotland can participate. Participants are approached through a range of methods including directly at outpatient clinics and general practitioners practices, leaflets with hospital letters and personal email from employers. Findings to date: SHARE has recruited around 130 000 people. SHARE has demonstrated that it can quickly and efficiently recruit to studies, over 20 until now. In addition, it can be used to administer questionnaire studies by email and recruit to patient and public involvement groups. Future plans: SHARE continues to steadily recruit with the ambition of eventually achieving 1 000 000 people in Scotland. We are steadily increasing the number of data sets we use for identifying participants. We are adding a mobile app which will facilitate dissemination about research and allow the collection of physiological and activity data if desired. We anticipate that SHARE will soon become the main source of health research recruitment in Scotland.